THE COMMODIFICATION OF POPULAR MUSIC IN DIGITAL ERA (Case Study of Music Label’s Sun Eater) - Noverdy Putra; Emeraldy Chatra; Elva Ronaning Roem; AB Sarca Putera (Jurnal Ranah Komunikasi, 2023)
The development of digital technology has changed the business structure of the music industry. The presence of social media and music streaming services adds to the size of the music industry itself, starting from the intersection of various actors (music labels, artists/musicians, music streaming service applications, music consumers), interests (business and state regulations), to power (distribution networks), especially in the perspective of the political economy of communication. In the context of this research, the object of research is the independent music label Sun Eater. This study uses a qualitative research method with an intrinsic case study approach. In line with that the data collection used is observation, in-depth interviews and documentation studies. The results of this study indicate that the content commodification carried out by Sun Eater as a music label is not focused on the music itself. But it wraps up the issues of today's youth and makes them like lyrics, pictures and videos. In audience commodification, Sun Eater does not put the audience as mere music fans. However, with a consumer-centric and data driven approach, Sun Eater treats their audience (music fans) like mass media, by “selling” back on advertisers on various digital platforms. Finally, the Commodification of Workers, that musicians are not just music workers. Moreover, Sun Eater places musicians as workers who have other responsibilities, ranging from filming digital content, interacting with fans on social media, to photo shoots with advertisers.